THE BIG FIVE PERSONALITY TRAITS AND SOCIODEMOGRAPHICS AS PREDICTORS OF MAJOR LIFE GOALS - Otašević, Biljana; Kodžopeljić, Jasmina (Primenjena psihologija, 2016)
The aim of this research was to investigate relations between major life goals and the Big Five personality traits. A total of 599 participants in the 16-72 age range completed the Big Five Inventory (BFI) and the Life Goal Questionnaire, which was designed for the purposes of this research. The principal component analysis showed the following seven life goal dimensions: Well-Being, Family Relations, Autonomy, Career, Relationships, Friendship, and Education. Psychometric and descriptive characteristics of each component were examined. Results of hierarchical regression analyses indicated a statistically significant, yet relatively small contribution of personality traits to prediction of major life goals, above and beyond the variance explained by the demographic predictor variables. The results were interpreted in terms of the findings of previous research, as well as considering the role of major life goals as characteristic adaptations within the Big Five model.